Date palms in Tunisia a follow-up study - Bioversity International; Gotor, Elisabetta (Bioversity International, 2013)
Over the millennia, desert dwellers have selected hundreds of different date palm varieties, each with particular characteristics. Currently, a single variety, the deglet nour, is favoured by the international market and is the most predominantly cultivated date palm in Tunisia threatening the long-term survival of alternative varieties and leading to genetic erosion. A Bioversity International project was implemented to encourage the diversification of date palms, as reliance on a single crop could threaten farmers’ future livelihoods if the vulnerable deglet nour were to fail due to pest and disease, or succumb to changes in market forces. This evaluation analyzes what impacts remain from the project 7 years beyond completion, and examines how the economic situation and the agricultural landscape of the farmers has evolved, with a view to determining valuable lessons for future project design. This publication is part of the Bioversity International’s series of Impact Assessment Briefs that aim to inform readers about the major results of evaluations carried out by the centre. The Briefs summarize conclusions and methods of more formal papers published in peer-reviewed journals.